Analisis Implementasi Regulasi dan Transparansi Proses Penganggaran APBKal pada Kalurahan Sendangadi Tahun 2025 - Ni Luh Gede Mertari Apta Daivi; Syifa Salsabela Apriyadi; Ananda Aliyah Salsabila; Farah Dhia Afandi (Jurnal Intelek Dan Cendikiawan Nusantara, 2026)
This study aims to analyze the implementation of regulations and transparency in the preparation of the Village Revenue and Expenditure Budget (APBKal) for Fiscal Year 2025 in Sendangadi Village, Sleman Regency. The study used a qualitative approach with descriptive analytical methods through document studies and interviews with key informants. The results of the study indicate that administratively, the preparation of the APBKal has complied with applicable provisions and has been able to reflect the principles of collaborative governance through a participatory Musrenbangkap mechanism involving the village government, the BPKal, and the community. Transparency in financial management has also been realized through the provision of budget information openly to the public. However, there is a gap between budget planning and implementation, which is influenced by central government policy intervention and suboptimal budget absorption, reflected in the high SILPA (Silpa). This condition indicates the need to improve synchronization between top-down policies and bottom-up needs, to support adaptive policy implementation. Overall, the implementation of regulations and transparency in the preparation of the APBKal in Sendangadi Village has been running well, but still requires optimization in the effectiveness of budget planning and implementation.